2017
DOI: 10.1038/s41467-017-00662-w
|View full text |Cite
|
Sign up to set email alerts
|

A method to identify trace sulfated IgG N-glycans as biomarkers for rheumatoid arthritis

Abstract: N-linked glycans on immunoglobulin G (IgG) have been associated with pathogenesis of diseases and the therapeutic functions of antibody-based drugs; however, low-abundance species are difficult to detect. Here we show a glycomic approach to detect these species on human IgGs using a specialized microfluidic chip. We discover 20 sulfated and 4 acetylated N-glycans on IgGs. Using multiple reaction monitoring method, we precisely quantify these previously undetected low-abundance, trace and even ultra-trace N-gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(102 citation statements)
references
References 54 publications
5
97
0
Order By: Relevance
“…These data are in line with and extend previous observations of Fab glycosylation in polyclonal anti‐citrullinated protein responses in RA, non‐expressed BCR sequences from CCP‐sorted cells, and a limited number of expressed monoclonals . In the current study, we also found that ACPA Fab glycans in the recombinant IgG were distinctly different from the Fc glycans and highly sialylated, consistent with what has been determined for Fab glycans of serum polyclonal antibodies in RA patients . Notably, a subset of the investigated mAbs have recently been found to have substantial in vitro and in vivo functionality and mediate enhanced osteoclastogenesis, pain behavior and endotoxin‐induced arthritis .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These data are in line with and extend previous observations of Fab glycosylation in polyclonal anti‐citrullinated protein responses in RA, non‐expressed BCR sequences from CCP‐sorted cells, and a limited number of expressed monoclonals . In the current study, we also found that ACPA Fab glycans in the recombinant IgG were distinctly different from the Fc glycans and highly sialylated, consistent with what has been determined for Fab glycans of serum polyclonal antibodies in RA patients . Notably, a subset of the investigated mAbs have recently been found to have substantial in vitro and in vivo functionality and mediate enhanced osteoclastogenesis, pain behavior and endotoxin‐induced arthritis .…”
Section: Discussionsupporting
confidence: 92%
“…The Fab glycopeptide profile of recombinantly expressed IgG from HEK‐293 cell systems cannot be expected to have the exact same glycan‐composition as what has been reported for PNGase F released Fab‐glycans analyzed from human polyclonal ACPA‐IgG . Yet, many of the complex sialylated forms identified herein have been detected in RA patients . In any case and more importantly, our results clearly indicate that the monoclonal IgG indeed have occupied high‐sialic acid Fab‐glycosylation sites.…”
Section: Resultssupporting
confidence: 71%
“…There have been few reports about triand tetra-antennary structures on human IgG. However, with the development of sensitive detection technologies, increasing numbers of trace glycans, including the tri-and tetra-antennary structures, have been observed on serum IgG, some of which have been identified as novel biomarkers for disease [37]. Our study findings suggest the high sensitivity of the lectin microarray will be useful for the discovery of trace glycans.…”
Section: Discussionmentioning
confidence: 64%
“…Conventionally, lectin‐based enrichment , hydrophilic interaction chromatography (HILIC) , porous graphitized carbon (PGC) and hydrazide based methods , are extensively used for the purification and enrichment of glycans. Over the past 5 years, several studies reported the use of a variety of materials to facilitate high‐throughput sample preparation .…”
Section: Advances In Glycan Purification Techniquesmentioning
confidence: 99%